2016
DOI: 10.1016/j.micres.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Phytogenic synthesis of silver nanoparticles, optimization and evaluation of in vitro antifungal activity against human and plant pathogens

Abstract: An attempt was made to synthesis of biocompatible silver nanoparticles from ten different Cassia spp. Among them, Cassia roxburghii aqueous leaf extract supported the synthesis of highly efficient and stable AgNPs. The synthesis of AgNPs was optimized at different physico-chemical condition and highly stable AgNPs were synthesized with 1.0mL of C. roxburghii leaf extract, pH 7.0, 1.0mM AgNO3 and at 37°C. The synthesized AgNPs were characterized by XPS, DLS and ZETA potential. DLS and ZETA potential analysis, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(67 citation statements)
references
References 24 publications
5
52
0
Order By: Relevance
“…against five different human pathogens A. niger, A. fumigatus, A. flavus, Penicillium sp. and Candidaalbicans [44]. These findings have confirmed the results that demonstrated the antifungal activity of AgNPs biosynthesized by lactic acid bacteria against spoilage fungi from genera Fusarium verticillioides, Penicillium expansum, A. flavus, and A. ochraceus [45].…”
Section: Antifungal Activity Of Agnpssupporting
confidence: 85%
“…against five different human pathogens A. niger, A. fumigatus, A. flavus, Penicillium sp. and Candidaalbicans [44]. These findings have confirmed the results that demonstrated the antifungal activity of AgNPs biosynthesized by lactic acid bacteria against spoilage fungi from genera Fusarium verticillioides, Penicillium expansum, A. flavus, and A. ochraceus [45].…”
Section: Antifungal Activity Of Agnpssupporting
confidence: 85%
“…In the present study, the leaf extracts of different plants were screened for the synthesis of AgNPs. To one ml of different leaf extracts, 9.0 ml of 1 mmol silver nitrate was mixed separately, and the tubes were incubated in dark conditions at room temperature for 24 h. The solution containing plant extracts and silver nitrate was monitored for colour change, precipitation and agglomeration of nanoparticles [22]. During the preliminary investigation, among the different plant extracts tested, the AgNPs synthesized using Peltophorum pterocarpum leaf extracts showed good stability and hence it was utilized for further studies.…”
Section: Screening Of Plant Extracts For Agnps Synthesismentioning
confidence: 99%
“…The AgNPs synthesized using Peltophorum pterocarpum leaf extracts were characterized using the UV-Visible spectrophotometer. The freshly synthesized AgNPs using plant extracts was analyzed for their maximum absorption spectra using UV-Visible spectrophotometer (U 2900, Hitachi) in the range of 300 to 700 nm [22].…”
Section: Uv-visible Spectroscopymentioning
confidence: 99%
“…These nanoparticles were further tested against human and plant pathogenic fungi, and they exhibited excellent result as compared to tested standard drugs. 139 Chandran et al 140 and Li et al 141 reported the synthesis of AgNPs from the leaf extracts of Aloe vera and Capsicum annum plants, respectively. The rapid synthesis of AgNPs using the fruit extract of Carica papaya was demonstrated, and it was found that the synthesized nanoparticles were highly toxic against different multidrug-resistant (MDR) human pathogens.…”
mentioning
confidence: 99%